Avaliação morfofuncional do rim de cães com e sem nefropatias submetidos a anestesia - Castro, Luma Tatiana Silva (2016)
Surgeries and anesthesia performed on dogs could cause kidney injury or worsen their renal functions if they are already sick. There is a literature gap in studies discussing post-surgery monitoring and its effects. This study aimed to evaluate dogs who undergone surgeries, in animals considered healthy and in those who had any renal alterations before surgery to evaluate if they developed any renal impairment due to surgery and anesthesia. Dogs were monitored and evaluated before and after surgeries in order to detect if they had any renal injury due to surgery or post-operative procedures. Evaluation took place right after the surgery and after certain time range from the surgery (Two, Seven, 28 and 90 days). Blood and Urine samples were drawn from the dogs to better classify them as healthy or having kidney injury. Consequently, hematological, urinary and blood gases profiles were proceeded. Few dogs with normal renal function that were submitted to surgery had transitory renal injury (23%). Nephropatic dogs that received specific therapy for renal protection did not presented tubular lesion due to surgery. Hypotension occurred in nephropatic dogs despite the use of non-hypotensive drug therapy but in a low frequency and had brief renal impairment. Anesthesia induced hypotension in non nephropatic dogs (54%) for the usage of hypotensive drug therapy.